2009
DOI: 10.3174/ajnr.a1563
|View full text |Cite
|
Sign up to set email alerts
|

Fenestrations of Intracranial Arteries Detected with 3D Rotational Angiography

Abstract: BACKGROUND AND PURPOSE:Fenestrations of intracranial arteries are variants resulting from incomplete fusion of primitive vessels. An association with aneurysms is suggested in many studies. On conventional angiography, fenestrations are rarely visible. 3D rotational angiography (3DRA) provides improved visualization of cerebral vessels from any desired angle. We used 3DRA to assess the frequency and location of fenestrations of intracranial arteries and a possible relationship with aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
61
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 13 publications
0
61
3
Order By: Relevance
“…Duplicated or fenestrated arteries are the second most common variants (after hypoplastic arteries) and are reportedly more frequent in the anterior circulation 15. The most commonly duplicated or fenestrated artery was AcomA , present in 4.4% of the cases in the present study in contrast to incidence of 32% observed by Milenkovic et al,(1985) 1 , and Ardkani et al, (2008) 8 .…”
Section: Discussioncontrasting
confidence: 50%
“…Duplicated or fenestrated arteries are the second most common variants (after hypoplastic arteries) and are reportedly more frequent in the anterior circulation 15. The most commonly duplicated or fenestrated artery was AcomA , present in 4.4% of the cases in the present study in contrast to incidence of 32% observed by Milenkovic et al,(1985) 1 , and Ardkani et al, (2008) 8 .…”
Section: Discussioncontrasting
confidence: 50%
“…However, a recent study using CT angiography 2) and 3D rotational angiography 27) demonstrated that the frequency of fenestrations was much more common at 11% to 26%, with the most frequent sites of fenestration in the vertebrobasilar system and anterior communicating region.…”
Section: Discussionmentioning
confidence: 99%
“…25) In a recent study, 3D rotational angiography failed to detect any A 1 fenestration. 27) Fenestrations may occur as a result of partial duplication, incomplete fusion, or the anomalous course of a nonvascular structure through the precursor vasculature or of a remnant of the plexiform anastomosis between the primitive olfactory artery and the ACA. 14,15, 18,20,24,25) The first autopsy case of aneurysm arising from the A 1 fenestration was described in 1962.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, recent studies with more frequent depiction of fenestrations including the present study suggest that a relation to aneurysms or other vascular pathology is not very likely. 7,8,10 Only large postmortem studies can provide a definite answer to this issue.…”
Section: Discussionmentioning
confidence: 99%
“…With 3D imaging, especially 3D rotational angiography, the detection rate of fenestrations has improved. 8 Scant data are available on the frequency and location distribution of fenestrations of intracranial arteries, to our knowledge. We used 3D rotational angiography of all intracranial arteries in a cohort of 179 patients with suspected intracranial aneurysms to assess the prevalence and location of fenestrations and the relation of fenestrations with aneurysms.…”
mentioning
confidence: 99%